INFLUENCE OF SOCIAL MEDIA ON THE TRAVEL INTENTION AMONG UTAR AND UiTM UNIVERSITY STUDENTS’ TRAVEL INTENTION TO SOUTH KOREA - Kwak Fang Yi; Teh Boon Teck; Edwin Michael; Farah Nabila Hamdan (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
Promoting travel destinations on social media is a common way of travel companies to promote the business as well as the company. This method attracts many youths who interested with travel to have the motivation and intention to travel to the destination. With the development of South Korean media entertainment industries, many youths ‘addicted’ in South Korean dramas, movies, and song. Social media as well as South Korean media entertainment industries lead Malaysian youths to have the intention to visit Korea. This study is to examine the effectiveness of social media apps in travel intention among Malaysian university students, and to explore the factors that lead Malaysian university students to have the motivation to travel to South Korea. Besides, to examine how social media and travel motivation influence Malaysian young adults is one of the objectives in this study as well. The significant of this study is showing the effectiveness of social media in influencing young adults in traveling. Besides, it could help the travel organizations to planning a strategy to attract young adults on social media.